2016
DOI: 10.5430/jnep.v7n1p45
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a simulated practice program in the construction of self-confidence for intervention in emergencies and its association with knowledge and performance

Abstract: The objective was to assess the impact of a simulated practice program on the construction of self-confidence for intervention in emergencies and its association with knowledge and performance. This is a quasi-experimental study without control group, with assessment before and after a 15-hour simulated practice program, in nursing students. The students' self-confidence increased significantly as a result of simulated practice with positive and statistically significant association between practical assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…“Making” is linked to cognitive aspects, skills and competencies for a given situation, that is, active participation is effective and promotes meaningful learning 36 . The experience of simulations proved to be positive in relation to the acquisition and increase of the level of confidence and learning 37-38 .…”
Section: Discussionmentioning
confidence: 92%
“…“Making” is linked to cognitive aspects, skills and competencies for a given situation, that is, active participation is effective and promotes meaningful learning 36 . The experience of simulations proved to be positive in relation to the acquisition and increase of the level of confidence and learning 37-38 .…”
Section: Discussionmentioning
confidence: 92%
“…A categoria onde foram mais sensíveis os índices de aumento da autoconfiança foi a dos enfermeiros [27]. Corroboraram ainda com esses resultados os estudos de diversos outros autores [23,28,30,36].…”
Section: Autoconfiançaunclassified
“…In most of the studies found in the scientific literature, the most intense use of simulation in the training of health professionals is noted and few works using this methodology for the training of health professionals in the work environment. In this sense, national and international studies were found describing the use of simulation in graduation for physicians (8)(9)(10) nurses (11)(12)(13)(14)(15)(16) , as well as for nursing technicians (17) . So far, no Brazilian studies have been published on training mediated by simulation with a multi-professional team in cardiorespiratory arrest (CRA) care.…”
Section: Introductionmentioning
confidence: 99%